Effects of cervical headgear appliance: a systematic review - Henriques,Fernanda Pinelli (2015)
OBJECTIVE: Although much has been investigated about the effects of cervical headgear, there remains some controversy. Therefore, the objective of this systematic review is to disclose the actual effects of the cervical headgear appliance, based on articles of relevant quality.METHODS: A literature review was conducted using PubMed, Web of Science, Embase, Scopus and Cochrane databases. Inclusion criteria consisted of human studies written in English; published between 1970 and 2014; in which only the cervical headgear was used to correct Class II malocclusion; prospective or retrospective; with a clear description of cervical headgear effects; with a sample size of at least 15 individuals. No comparative studies, clinical cases or cases with dental extractions were included and the sample should be homogeneous.RESULTS: Initially, 267 articles were found. A total of 42 articles were selected by title and had their abstracts read. Finally, 12 articles were classified as with high quality and were used in this systematic review.CONCLUSIONS: The cervical headgear appliance proved efficient to correct Class II, Division 1 malocclusion. Its effects consisted in correction of the maxillomandibular relationship by restriction of maxillary anterior displacement; distalization and extrusion of maxillary molars; and slight maxillary expansion.